Ant-Neointimal Formation Effects of SLC6A6 in Preventing Vascular Smooth Muscle Cell Proliferation and Migration via Wnt/β-Catenin Signaling - Rong, Zhihua; Li, Fengshi; Zhang, Rui; Niu, Shuai; Di, Xiao; Ni, Leng; Liu, Changwei (International journal of molecular sciences, 2023)
Vascular smooth muscle cells (VSMCs) play an important role in the pathogenesis of vascular remolding, such as atherosclerosis and restenosis. Solute carrier family 6 member 6 (SLC6A6) is a transmembrane transporter that maintains a variety of physiological functions and is highly expressed in VSMCs. However, its role on VSMCs during neointimal formation remains unknown. In this study, mRNA and protein levels of SLC6A6 were examined using models of VSMC phenotype switching in vivo and in vitro and human artery samples with or without atherosclerosis. SLC6A6 gain- and loss-of-function approaches were performed by adenovirus infection or small interfering RNA (siRNA) transfection, respectively. Reactive oxygen species (ROS), proliferation, migration, and phenotype-related proteins of VSMCs were measured. Vascular stenosis rate and related genes were assessed in a rat vascular balloon injury model overexpressing SLC6A6. SLC6A6 was downregulated in dedifferentiated VSMCs, atherosclerotic vascular tissues, and injured vascular tissues. SLC6A6 suppressed VSMC proliferation and migration, while increasing contractile VSMC proteins. Mechanistically, SLC6A6 overexpression reduced ROS production and inhibited the Wnt/β-catenin pathway. Furthermore, SLC6A6 overexpression suppressed neointimal formation in vivo. Collectively, overexpression of SLC6A6 suppresses neointimal formation by inhibiting VSMC proliferation and migration via Wnt/β-catenin signaling and maintaining the VSMC contractile phenotype.